Development and validation of a survey to measure features of clinical networks. Issue 1 (December 2016) - Brown, Bernadette; Haines, Mary; Middleton, Sandy; Paul, Christine; D'Este, Catherine; Klineberg, Emily; Elliott, Elizabeth
Abstract Background Networks of clinical experts are increasingly being implemented as a strategy to improve health care processes and outcomes and achieve change in the health system. Few are ever formally evaluated and, when this is done, not all networks are equally successful in their efforts. There is a need to formatively assess the strategic and operational management and leadership of networks to identify where functioning could be improved to maximise impact. This paper outlines the development and psychometric evaluation of an Internet survey to measure features of clinical networks and provides descriptive results from a sample of members of 19 diverse clinical networks responsible for evidence-based quality improvement across a large geographical region. Methods Instrument development was based on: a review of published and grey literature; a qualitative study of clinical network members; a program logic framework; and consultation with stakeholders. The resulting domain structure was validated for a sample of 592 clinical network members using confirmatory factor analysis. Scale reliability was assessed using Cronbach's alpha. A summary score was calculated for each domain and aggregate level means and ranges are reported. Results The instrument was shown to have good construct validity across seven domains as demonstrated by a high level of internal consistency, and all Cronbach's α coefficients were equal to or above 0.75. In the survey sample of network members there was strong reported commitment and belief in network-led quality improvement initiatives, which were perceived to have improved quality of care (72.8 %) and patient outcomes (63.2 %). Network managers were perceived to be effective leaders and clinical co-chairs were perceived as champions for change. Perceived external support had the lowest summary score across the seven domains. Conclusions This survey, which has good construct validity and internal reliability, provides a valid instrument to use in future research related to clinical networks. The survey will be of use to health service managers to identify strengths and areas where networks can be improved to increase effectiveness and impact on quality of care and patient outcomes. Equally, the survey could be adapted for use in the assessment of other types of networks.